“IF I AM SURE TO DO THAT NOW, ...” PENYUSUNAN UNI PROCRASTINATION SCALE (UPS) - Setiawan, Indra (University of Surabaya, 2013)
Procrastination is the irrational delay (Steel, 2007). Behavior delays can be measured through attitude scale. Irrational Procrastination Scale (IPS) is a scale that measures of procrastination. IPS empirically measure Irrational Delay, but there are two aspects of the Indonesian version. Procrastinatory cognitions Inventory (PCI) is a scale that measures aspects of procrastination Iratinal Belief. PCI and IPS have the same irrational aspects, namely, the common factor for these two scales were restructured as new prokrastiasi scale better quality. The study was conducted in two phases. The first phase, aimed to develop a new scale. The second phase aims to test the reliability and validity. Phase preparation using 199 participants from social networks, while testing phase aimed at 33 participants were students of psychology faculty. Common factors of the preparation phase produces a new scale called procrastination Union Scale (UPS). UPS correlation figure is higher than the correlation PCI and IPS. Conceptually, UPS is correlated with aspects of TMT Expectancy (E), Value (V), Impulsifity (I).